Analisis Kerusakan Lapis Permukaan Jalan dengan Metode Pavement Condition Index (PCI) pada Jalan Prof. Syarief Thayeb Kota Langsa - Saputra, Joeny; Rajib Muammar; Iqbal (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2026)
Road infrastructure is a vital land transportation facility that plays an important role in supporting economic growth and socio-cultural development. Prof. Syarief Thayeb Road experiences heavy traffic conditions and is frequently passed by overloaded vehicles, such as student buses and trucks transporting palm oil, which contribute to pavement deterioration. This study aimed to analyze the types of pavement distress on the road surface, determine the level of road damage using the Pavement Condition Index (PCI) method, and identify appropriate maintenance actions and solutions for the Prof. Syarief Thayeb Road section based on its damage condition. In the PCI method, pavement distress severity is evaluated based on three main factors, namely distress type, severity level, and distress density. The PCI provides a numerical index ranging from 0 to 100, where 0 indicates failed pavement condition and 100 indicates excellent pavement condition. The pavement condition assessment was conducted through field surveys to identify and record surface distress. The types of damage identified along the 2 km section of Prof. Syarief Thayeb Road included alligator cracking, patching, potholes, and rutting. The analysis results showed that the PCI value for the observed road section was 81.15, which falls into the very good category, indicating that only routine maintenance is required for roads with PCI values between 41 and 81. Recommended repair methods for alligator cracking include partial-depth or full-depth patching, surface layer improvement, and overlay application. Pothole repairs involve partial-depth and full-depth patching, while rutting repairs include shallow partial patching, full-depth patching, and surface layer improvement followed by an additional overlay.